aBVA Procedure by Uniportal Video-Assisted Thoracoscopic Surgery for Right Upper Peripheral Lung Cancer: A Randomized Trial - Wang, Kaiying; Zhang, Jian; Li, Jianglun; Liu, Langbo; Tang, Zhongben; Du, Xiaojun (Frontiers in Oncology, 2022)
Objective This study aims to determine the optimal dividing order of anatomic pulmonary resection under uniportal video-assisted thoracoscopic surgery (uni-VATS) for patients with right upper peripheral lung cancer. Methods Patients who met the eligibility criteria were randomly allocated into the aBVA and VAB groups. In the aBVA group, the surgical procedure proceeded from the posterior to the anterior region (from the deeper to the superficial site). In the VAB group, the dissection orders were vein first followed by arterial branches, followed by the bronchus. Clinical data were collected and analyzed. Results Sixty patients were randomly allocated to the aBVA group (n = 30) and the VAB group (n = 30). The operation time in the aBVA group (230.500 ± 68.360 min) was significantly shorter than that in the VAB group (305.600 ± 107.821 min) (p = 0.01). The blood loss in the aBVA group (104.000 ± 70.935 ml) was significantly lower than that in the VAB group (391.000 ± 625.175 ml) (p = 0.01). Two patients in the VAB group underwent conversion to 2-portal VATS. The number of lymph nodes (13.367 ± 5.436 vs. 10.333 ± 7.279, p = 0.072) and lymph node stations (5.067 ± 1.574 vs. 4.467 ± 2.345, p = 0.567) were comparable between the two groups. The differences in the postoperative drainage tube time (5.033 ± 3.113 vs. 6.467 ± 4.447 days, p = 0.278) and hospital stay (8.233 ± 3.390 vs. 9.433 ± 4.523 days, p = 0.361) were not significantly different between the two groups. Conclusion Compared with the VBA procedure, aBVA is easier for patients with right upper peripheral lung cancer who undergo uni-VATS lobectomy.